1998
DOI: 10.1177/026765919801300305
|View full text |Cite
|
Sign up to set email alerts
|

The influence of mannitol on renal function during and after open-heart surgery

Abstract: Mannitol is often included in the priming solution of the heart-lung machine used during cardiopulmonary bypass (CPB). This study was set up to evaluate the effect of different doses of mannitol on human patients. Patients receiving 10 g of mannitol (n = 18) had an increased diuresis only during the bypass period (mean time = 87 min) when compared with a control group (n = 19) who did not receive mannitol. Patients receiving 20 g of mannitol (n = 19) had a significantly greater diuresis than both the control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 17 publications
0
23
1
1
Order By: Relevance
“…Despite this, the renal outcomes associated with the use of mannitol in cardiac surgery are mixed (210)(211)(212)(213). There are some data suggesting that atrial natriuretic peptide (214) and B-type natriuretic peptide (215) may be of benefit in patients undergoing cardiac surgery.…”
Section: Current and Future Pharmacologic Strategiesmentioning
confidence: 99%
“…Despite this, the renal outcomes associated with the use of mannitol in cardiac surgery are mixed (210)(211)(212)(213). There are some data suggesting that atrial natriuretic peptide (214) and B-type natriuretic peptide (215) may be of benefit in patients undergoing cardiac surgery.…”
Section: Current and Future Pharmacologic Strategiesmentioning
confidence: 99%
“…Nearly 40% of cardiac units in the UK use mannitol as a component of the bypass pump prime [7]. Mannitol is freely filtered by the glomeruli, with a plasma half-life of 2.5 h [8], and <7% is reabsorbed [9], resulting in an increase in the osmotic pressure of the glomerular filtrate to produce a diuresis. The osmotic effect also reduces glomerular and tubular oedema, helping to restore glomerular blood flow and aid removal of intraluminal obstructions [8].…”
mentioning
confidence: 99%
“…Mannitol is freely filtered by the glomeruli, with a plasma half-life of 2.5 h [8], and <7% is reabsorbed [9], resulting in an increase in the osmotic pressure of the glomerular filtrate to produce a diuresis. The osmotic effect also reduces glomerular and tubular oedema, helping to restore glomerular blood flow and aid removal of intraluminal obstructions [8]. Mannitol increases renal blood flow [9,10] and may also scavenge oxygen free radicals, which reduces injury to the renal brush border membrane [10].…”
mentioning
confidence: 99%
“…However, several other studies did not confirm these findings, and the potential role of mannitol remains unclear . In fact, Carcoana et al [28] showed an increased urinary excretion of ß-2 microglobulin in patients who received mannitol and dopamine, suggestive of increased tubular injury in this group. Sirivella et al randomly assigned 100 patients with postoperative oliguric or anuric renal failure to therapy with either intermittent doses of loop diuretics or a continuous infusion of mannitol, furosemide, and dopamine (2 mg/kg per min).…”
Section: General Measures To Prevent Renal Dysfunction After Cardiac mentioning
confidence: 87%